2014
DOI: 10.1007/s00774-014-0612-8
|View full text |Cite
|
Sign up to set email alerts
|

Bruton tyrosine kinase (Btk) suppresses osteoblastic differentiation

Abstract: The Tec family of nonreceptor tyrosine kinases has been shown to play a key role in inflammation and bone destruction. Bruton tyrosine kinase (Btk) has been the most widely studied because of its critical role in B cells. Furthermore, recent evidence has demonstrated that blocking Btk signaling is effective in ameliorating lymphoma progression and experimental arthritis. The role of Btk in osteoblastic differentiation has not been well elucidated. In this study, we demonstrated the role of Btk in osteoblastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…LFM is a potent and selective inhibitor of Bruton’s tyrosine kinase (Btk) [ 51 , 52 , 53 ]. Btk suppresses the osteogenic differentiation of MC3T3-E1 cells, primary calvarial osteoblasts, and bone marrow stromal ST2 cells [ 54 ], which supports the present results. Btk regulates osteoblastic differentiation through the MAPK, NF-κB, and protein kinase C (PKC) α signaling pathways [ 54 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…LFM is a potent and selective inhibitor of Bruton’s tyrosine kinase (Btk) [ 51 , 52 , 53 ]. Btk suppresses the osteogenic differentiation of MC3T3-E1 cells, primary calvarial osteoblasts, and bone marrow stromal ST2 cells [ 54 ], which supports the present results. Btk regulates osteoblastic differentiation through the MAPK, NF-κB, and protein kinase C (PKC) α signaling pathways [ 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…Btk suppresses the osteogenic differentiation of MC3T3-E1 cells, primary calvarial osteoblasts, and bone marrow stromal ST2 cells [ 54 ], which supports the present results. Btk regulates osteoblastic differentiation through the MAPK, NF-κB, and protein kinase C (PKC) α signaling pathways [ 54 ]. In addition, Btk is a negative regulator of Wnt–β-catenin signaling in B cells [ 55 ].…”
Section: Discussionsupporting
confidence: 90%
“…Integration of methylation and gene expression data corresponding to the Homeobox and bone formation-related genes revealed that both DNA hyper-and hypo-methylation events were associated with both gene downregulation and upregulation ( Figure 2C). Specifically, hypermethylated genes that showed a reduced expression in patient MSCs include positive regulators of OB differentiation such as RUNX2 or NRP2 34 ( Figure 2C) In contrast, negative regulators of osteogenesis such as SFRP2 35 or NFATC2 36 were hypomethylated and consequently upregulated in patient MSCs. In all, these factors could potentially contribute to impaired osteoblastogenesis associated to bone disease in MM and this is summarized in Supplementary Table S7).…”
Section: Aberrant Dna Methylation Is Associated With Differential Hommentioning
confidence: 99%
“…The results of this study indicate that Btk enhanced the differentiation of osteoclasts in an inflammatory environment, which was mainly achieved by regulating the expression of PLC γ 2 and NFATc-1. Previous studies have also shown that in addition to the regulation of osteoclast differentiation, Btk can also regulate MAPK, NF- κ B, and PKC α signaling to suppress osteoblastic differentiation [31].…”
Section: Discussionmentioning
confidence: 99%